OsPHS1 is required for both male and female gamete development in rice. (December 2022) - Yu, Hao; Zhang, Liping; He, Xiaojuan; Zhang, Taohui; Wang, Chaolong; Lu, Jiayu; He, Xiaodong; Chen, Keyi; Gu, Weihang; Cheng, Siqi; Hu, Yang; Yao, Bowen; et al.
Abstract: Meiosis plays an essential role in the production of male and female gametes. Extensive studies have elucidated that homologous chromosome association and pairing are essential for crossing-over and recombination of chromosomal segments. However, the molecular mechanism of chromosome recognition and pairing remains elusive. Here, we identified a rice male–female sterility mutant plant. Cytological observations showed that the development of both pollen and embryo sacs of the mutant were abnormal due to defects in homologous chromosome recognition and pairing during prophase I. Map-based cloning revealed that Os06g0473000 encoding a poor homologous synapsis 1 (PHS1) protein is the candidate target gene, which was confirmed by knockout using CRISPR/Cas9 technology. Sequence analysis revealed a single base mutation (G > A) involving the junction of the fourth exon and intron of OsPHS1, which is predicted to alter splicing, resulting in an Osphs1 mutant. Expression pattern analysis indicated that OsPHS1 expression levels were mainly expressed in panicles at the beginning of meiosis. Subcellular localization analysis demonstrated that the OsPHS1 protein is situated in the nucleus and cytoplasm. Taken together, our results suggest an important role for OsPHS1 in homologous chromosome pairing in both male and female gametogenesis in rice. Highlights: The important role of the OsPHS1 in homologous chromosomes recognition and pairing in meiotic prophase.